The English Translation Of Your Phrase Is: “Post-Covid-19 Lung Changes And Rehabilitation Methods” (Texas Journal of Medical Science, 2025)
This article analyzes the significance, types, and objectives of the rehabilitation process after COVID-19. Rehabilitation plays a crucial role in restoring physical, cognitive, and mental health, as well as improving the quality of daily life for patients. The article highlights key areas such as physical therapy, occupational therapy, speech therapy, pulmonary rehabilitation, and mental health therapy. It also provides information on developing individualized rehabilitation plans, assessing patients’ needs, and monitoring recovery progress. The recommendations emphasize the importance of a personalized approach, interdisciplinary collaboration among healthcare professionals, and social support. Rehabilitation is considered a key factor in returning to a healthy life, regaining independence, and enhancing psychological resilience after COVID-19.